Untersuchung der Photooxidantien Wasserstoffperoxid, Methylhydroperoxid und Formaldehyd in der Troposphäre der Antarktis - Riedel, Katja (Univ. Bremen, 2001)
Photooxidants play an important role for the oxidation capacity of the troposphere. The presented work deals with seasonal changes of atmospheric photooxidants like hydrogen peroxide (H2O2), methylhydroperoxide (MHP) and formaldehyde (HCHO). The principal purpose was to follow and quantify the mixing-ratios of these photochemical species for the first time over a complete annual cycle in Antarctica. During two field campaigns at the German Antarctic station Neumayer (overwintering campaign from January 1997 until March 1998 and a shorter campaign from January to March 1999) continuous measurements of atmospheric mixing-ratios were performed. A continuous wet-chemical technique was used for peroxides and formaldehyde sampling and analysis. Species were quantified by fluorescence detection. In order to compare the results and measurements with well-known reaction mechanisms a photochemical box model was applied. The obtained time series show a pronounced seasonal variation with higher values during summer. For the first time atmospheric concentrations of H2O2, MHP and HCHO were documented during polar night in winter. The mixing-ratios were significantly higher than expected due to missing actinic radiation essential for photochemical production. Trajectory analyses and calculations with a three-dimensional model showed that during winter the mixing-ratios of photooxidants are mainly affected by long-range transport in the free troposphere. Investigations during the Antarctic ó́zone hole period ́́show no significant impact of the increased UV-B radiation on the photooxidants. The findings of this work contribute to a better understanding of the photochemistry of the investigated trace gases in the clean troposphere of Antarctica and provide a useful data record for further photochemical modeling. : thesis